2014
DOI: 10.3109/10520295.2014.894575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high fat diet induced obesity on peripheral nerve regeneration and levels of GAP 43 and TGF-β in rats

Abstract: The increasing frequency of obesity is important because of its accompanying related health problems. The effects of obesity on peripheral nerves have not been elucidated. We investigated the effects of obesity on sciatic nerve regeneration using electrophysiology, stereology, immunohistochemistry, histopathology and functional tests. We used control, obese, control injured and obese injured groups of rats. Electrophysiological results showed that nerve conduction velocity and EMG were same in the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Obesity is caused by complex genetic and environmental factors and has been found to be a risk factor for various diseases, including DM, HTN, hyperlipidemia, coronary heart disease (CHD), stroke, kidney disease and cancer. Obesity has been reported to reduce the quantity and effectiveness of growth factors, delaying regeneration of damaged sciatic nerves and recovery …”
Section: Discussionmentioning
confidence: 99%
“…Obesity is caused by complex genetic and environmental factors and has been found to be a risk factor for various diseases, including DM, HTN, hyperlipidemia, coronary heart disease (CHD), stroke, kidney disease and cancer. Obesity has been reported to reduce the quantity and effectiveness of growth factors, delaying regeneration of damaged sciatic nerves and recovery …”
Section: Discussionmentioning
confidence: 99%
“…This finding was confirmed by Lee et al [13] who explained that patients with higher BMIs have poor physical fitness. Moreover, it was suggested that obesity may negatively affect peripheral nerve regeneration [1].…”
Section: Discussionmentioning
confidence: 99%
“…Then, sections were washed three times with PBS and incubated with biotinylated anti-rabbit IgG for a period of 30 min at 37 C. Immunological activity was detected with a streptavidin-biotin complex kit (ScyTek Laboratories, SitoGen Biomedikal Ltd; _ Istanbul, Turkey) and developed with diaminobenzidine tetrahydrochloride. The sections were counterstained with Mayer hematoxylin and images are obtained under a light microscope (Leica LMD 7000, Leica Inc) [Bekar et al 2014]. …”
Section: Tunel Assaymentioning
confidence: 99%